Fangyukangsuan granules ameliorate hyperuricemia and modulate gut microbiota in rats - Zhang, Qing-zheng; Zhang, Ji-rui; Li, Xue; Yin, Jin-long; Jin, Li-ming; Xun, Zhuo-ran; Xue, Hao; Yang, Wan-qi; Zhang, Hua; Qu, Jingyong; Xing, Zhi-kai; Wang, Xu-min (Frontiers in Immunology, 2024)
Hyperuricaemia (HUA) is a metabolic disorder characterised by high blood uric acid (UA) levels; moreover, HUA severity is closely related to the gut microbiota.HUA is also a risk factor for renal damage, diabetes, hypertension, and dyslipidaemia; however, current treatments are associated with detrimental side effects. Alternatively, Fangyukangsuan granules are a natural product with UAreducing properties. To examine their efficacy in HUA, the binding of small molecules in Fangyukangsuan granules to xanthine oxidase (XOD), a key factor in UA metabolism, was investigated via molecular simulation, and the effects of oral Fangyukangsuan granule administration on serum biochemical indices and intestinal microorganisms in HUA-model rats were examined. Overall, 24 small molecules in Fangyukangsuan granules could bind to XOD. Serum UA, creatinine, blood urea nitrogen, and XOD levels were decreased in rats treated with Fangyukangsuan granules compared to those in untreated HUA-model rats.Moreover, Fangyukangsuan granules restored the intestinal microbial structure in HUA-model rats. Functional analysis of the gut microbiota revealed decreased amino acid biosynthesis and increased fermentation of pyruvate into short-chain fatty acids in Fangyukangsuan granule-treated rats. Together, these findings demonstrate that Fangyukangsuan granules have anti-hyperuricaemic and regulatory effects on the gut microbiota and may be a therapeutic candidate for HUA.